THE INFLUENCE OF AUDITOR’S PROFESSIONAL SKEPTICISM AND COMPETENCE ON FRAUD DETECTION: THE ROLE OF TIME BUDGET PRESSURE - Said, Lola Luviana; Munandar, Agus (UI Scholars Hub, 2018)
This study aims to examine the moderating effect of time budget pressure on the influence of the independent auditor’s professional skepticism and competence on fraud detection. This study uses a survey approach in the form of a questionnaire filled by 103 external auditors in Jakarta as respondents. The results indicate that if auditors have a high level of professional skepticism and competence, then the probability of fraud that will be detected is also high. Furthermore, time budget pressure cannot moderate the influence of auditor competence on fraud detection. This means that no matter how tight the time budget pressure that is faced by auditors, as long as they have competence, the detection of fraud by the auditor is still possible. Conversely, the results also show that auditors who have high professional skepticism cannot detect fraud if there is a time budget pressure. The results are expected to provide an input to auditors that they need to give more attention and consideration to the time budget assignment when signing a contract with the client.